Factors affecting the effectiveness training in Majlis Perbandaran Kajang staffs / Nazatul Haziqah Zainal Alam - Zainal Alam, Nazatul Haziqah (Faculty of Business and Management, 2014)
The aim study is to examine the factors affecting the effectiveness training in Majlis Perbandaran Kajang staffs. The objectives of this study about the levels of the factors affecting the effectiveness training in Majlis Perbandaran Kajang. Besides that, to know the most factors that influences the factor affecting the effectiveness training in Majlis Perbandaran Kajang. Respondent for this research were grade C and D staffs in Majlis Perbandaran Kajang. Questionnaire was used as the instruments to collect the data. The data will be analyze by using Statistical Package for Social Science (SPSS),